Analysis of the Cardiology Outpatient Service System at RSUD Majalaya: Implementation of SIMRS and Online Registration to Improve Service Quality - Sofiyani, Oktaria; Susanti , Ai Susi (Asian Journal of Environmental Research, 2025)
This study aims to analyze the service system in the Cardiology Clinic of RSUD Majalaya, with a specific focus on the implementation of the Hospital Management Information System (SIMRS) and online registration services. The background of this research is based on the increasing demand for efficient and high-quality healthcare services, particularly in specialist clinics that experience high patient volumes on a daily basis. Efficient service delivery is essential to ensure patient satisfaction, reduce overcrowding, and optimize clinical workflows. This research employed a qualitative descriptive method, involving direct observation of service processes and in-depth interviews with administrative staff and patients. The findings indicate that the implementation of SIMRS and the online registration system has significantly contributed to the acceleration of administrative processes, reduced patient waiting times, and improved the overall quality of service. Patients who utilized the online registration system reported shorter queues and a more organized experience. However, several challenges remain, particularly regarding limited digital literacy among a segment of the patient population, as well as technical constraints related to internet connectivity and server stability. These issues can hinder the full utilization of digital services. Based on the findings, it is recommended that the hospital invest in continuous infrastructure improvements, provide digital literacy training or assistance for patients, and conduct periodic evaluations of system performance. Such measures are essential to ensure the long-term effectiveness and sustainability of digital healthcare services, thereby enhancing the patient experience and supporting overall healthcare delivery goals.